Program Penerapan Teknologi Tepat Guna Implementasi ASTER (Alat Silase Terkompartemen) untuk Peternak Domba di Wilayah Kadudampit Kabupaten Sukabumi - suhendar suhendar (Bahasa Indonesia, 2018)
Abstract The application of Appropriate Technology to the Community was carried out in Kadudampit District, Sukabumi Regency, West Java Province. As the sub-district mapped to be one of the centers of sheep farmers by the Sukabumi Regency government, the farmers have problems with the availability of fresh forage which is limited during the dry season. They also do not have the ability to make silage and design silage tools that are truly effective and efficient. The aim of this program is to provide information and skills to the sheep breeders group about silage feed technology, design and use of the Compartment Silage Tool (ASTER). This program is carried out through seven stages, including: 1) Activity Socialization; 2) Design of the Compartment Silage Tool Implementation; 3) Assembling the Compartment Silage Tool; 4) Compartment Silage Tool Operation Test; 5) Operational Assistance and Completion of the Compartment Silage Tool; 6) Application and grant of Compartment Silage Tool; and 7) the monitoring and evaluation stage, aims to see the progress and achievements of each stage of the program so that all programs can be carried out according to the objectives. Abstrak Penerapan Teknologi Tepat Guna Kepada Masyarakat ini dilakukan di Kecamatan Kadudampit, Kabupaten Sukabumi Provinsi Jawa Barat. Sebagai kecamatan yang dipetakan menjadi salah satu sentra peternak domba oleh pemerintah Kabupaten Sukabumi, para peternaknya memiliki masalah akan ketersediaan pakan hijauan segar yang terbatas pada saat musim kemarau. Mereka juga tidak memiliki kemampuan membuat silase serta merancang alat silase yang benar-benar efektif dan efisien. Tujuan dari program Penerapan Teknologi Tepat Guna Kepada Masyarakat ini adalah memberikan sosialisasi dan keterampilan kepada kelompok peternak domba tentang teknologi pakan silase, perancangan dan penggunaan Alat Silase Terkompartemen (ASTER). Program ini dilakukan melalui tujuh tahap, antara lain: 1) Sosialisasi Kegiatan; 2) Perancangan Implementasi Alat Silase Terkompartemen; 3) Perakitan Alat Silase Terkompartemen; 4) Uji Operasi Alat Silase Terkompartemen; 5) Pendampingan Operasional dan Penyempurnaan Alat Silase Terkompartemen; 6) Penerapan dan menghibahkan Alat Silase Terkompartemen; dan 7) tahap monitoring dan evaluasi, bertujuan melihat progres dan capaian setiap tahapan program ini agar seluruh program dapat terlaksana sesuai tujuan.